1991
DOI: 10.3168/jds.s0022-0302(91)78293-3
|View full text |Cite
|
Sign up to set email alerts
|

Slow Release Somatotropin in Dairy Heifers and Cows Fed Two Levels of Energy Concentrate. 2. Plasma Hormones and Metabolites

Abstract: Fifty Holstein dairy cows (26 primiparous) were used to evaluate effects of level of concentrate and of slow release recombinant bST on plasma hormones and metabolites. Blood was sampled at wk 14 and 20 of lactation, which was 5 and 11 wk after the first bST injection. In addition, at d 3 and 10 after the third bST injection, diurnal profiles of somatotropin and metabolites were studied in 7 bST cows and 5 control cows by blood sampling every 20 min over 6 h. Supplementation by bST enhanced plasma somatotropin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
3
14
2
1
Order By: Relevance
“…Lower concentrations of T3 were found in primiparous cows which is in disagreement with the data of Cissé et al (1991) who suggested that higher T3 concentrations in the first lactation could be due to a lower milk yield since thyroid hormones are excreted by the mammary gland. On the other hand, a lower level of T3 was reported to be associated with lower EB (Blum et al 1983), which seems to be the case in our study when taking into account the fact that primiparous cows presented comparatively greater body condition loss and an overall unbalanced metabolic condition.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Lower concentrations of T3 were found in primiparous cows which is in disagreement with the data of Cissé et al (1991) who suggested that higher T3 concentrations in the first lactation could be due to a lower milk yield since thyroid hormones are excreted by the mammary gland. On the other hand, a lower level of T3 was reported to be associated with lower EB (Blum et al 1983), which seems to be the case in our study when taking into account the fact that primiparous cows presented comparatively greater body condition loss and an overall unbalanced metabolic condition.…”
Section: Discussioncontrasting
confidence: 90%
“…On the other hand, a lower level of T3 was reported to be associated with lower EB (Blum et al 1983), which seems to be the case in our study when taking into account the fact that primiparous cows presented comparatively greater body condition loss and an overall unbalanced metabolic condition. This could explain the apparent discrepancy with the study of Cissé et al (1991), in which heifers and cows had the same EBs. Low thyroid hormone concentrations have been suggested to be associated with low reproductive performance in the postpartum cow (Huszenicza et al 2002).…”
Section: Discussioncontrasting
confidence: 76%
“…This pattern is relatively well known in ruminants, particularly the increase after the meal (Manston et al 1981;Cisse et al 1991;Clement et al 1991). In animals undergoing starvation or undernutrition, as those in group 1, the mobilisation and utilisation of amino acids for glucose and oxaloacetate production are increased, which is reflected in high URE values between 03:00 and 17:00 h (Cocimano and Leng 1967;Gaál et al 1993).…”
Section: Ureamentioning
confidence: 83%
“…In addition, several studies presented a diurnal rhythm for glucose, insulin, NEFA and BHBA in ruminants [83][84][85]. Especially, plasma NEFA levels seem to be more sensitive and variable before feeding compared to after feeding.…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 99%